Understanding of Animal Science Students on Livestock Fiqh : Case Study Students of Animal Science Department State Agricultural Polytechnic Pangkajene Kepulauan, South of Sulawesi, Indonesia - Sukriya, Aminata; Sari, Anita; Fasiha, Fasiha (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2024)
-Purpose Conceptual understanding is an ability to receive, absorb, and comprehend materials or information acquired through a series of events that can be directly observed or heard, stored in the mind, and later applied in daily life. This research aims to describe the level of conceptual understanding of Fiqh (Islamic jurisprudence) among students majoring in Animal Husbandry at Politani Pangkep. -Method The research employed a descriptive analythic method with a survey approach. The data collection technique used in this study involved an objective test consisting of multiple-choice questions with four alternative answers which was distributed to senior undergraduates students on animal science department State Polytechnic of Agriculture Pangkajene Kepulauan, The data analysis technique using descriptive qualitative.. -Result The research results indicate that the overall average scores of Animal Husbandry students at Politani Pangkep fall within the sufficient or less category when assessed against standard criteria. Consequently, it can be concluded that the low level of conceptual understanding among students is caused by several factors, including the omission of Fiqh animal husbandry lessons from the curriculum, lecturers predominantly using lecture methods in teaching, a lack of learning resources, and students' insufficient interest in the field of Fiqh. -Implication a robust understanding of livestock fiqh has significant implications for ensuring the authenticity, quality, and integrity of the Halal industry. Individuals with this knowledge can contribute to effective certification processes, quality assurance, oversight, and community trust, ultimately supporting the growth and sustainability of the Halal market.